A longitudinal examination of African American adolescent females detained for status offense. (January 2020) - Kim, Bo-Kyung Elizabeth; Quinn, Camille R.; Logan-Greene, Patricia; DiClemente, Ralph; Voisin, Dexter
Highlights: Detaining youth with status offense (e.g., truancy, runaway) is prohibited by law. African American adolescent girls are detained at higher rates for status offenses. One third of African American girls were detained for status offense. Status offenders were exposed to higher peer risk profiles. At follow-up, nearly 39% of status offenders reported re-confinement. Abstract: Introduction: Behaviors like truancy, running away, curfew violation, and alcohol possession fall under the status offense category and can have serious consequences for adolescents. The Juvenile Justice and Delinquency and Prevention Act prohibited detaining status offenders. We explored the degree to which African American adolescent girls were being detained for status offenses and the connections to their behavioral health risks and re-confinement. Methods: 188 African American girls (aged 13–17), recruited from detention facilities, were surveyed at baseline and 3-month follow-ups. Logistic regression models estimated the likelihood of longitudinal re-confinement, controlling for sexual and behavioral health risk factors. Results: One third of the overall sample was detained for a status offense. Status offenders were exposed to higher peer risk profiles. At follow-up, nearly 39% of status offenders reported re-confinement. Compared to youth with other offenses, those who violated a court order (type of status offense) were 3 times more likely to be re-confined. Controlling for sexual and behavioral health risk factors, the odds of re-confinement was not statistically significant. Conclusion: Overall findings suggest that c ourts and detention facilities must devote specialized resources to addressing the socio-behavioral needs of African American girls with status offenses so as not to use detention as an intervention.